ANALISIS PENGARUH NILAI WISATA TERHADAP KEPUASAN KONSUMEN DI PESONA KAMPUNG SUNDA BANDUNG BARAT - Adithya Abiwardani (International Journal of Entrepreneurship and Tourism, 2024)
ABSTRACT The desire to travel and taste unique and authentic food is emerging as a new phenomenon in the tourism industry. Historically, hospitality services (food, beverage and accommodation) have served a supporting role in the larger tourism industry. This study was conducted to determine the effect of culinary tourism values on customer satisfaction at the Pesona Kampung Sunda Bandung Restaurant located at Jl.Cisangkuy No.56, Citarum, Bandung City. This research method uses a quantitative method which is a method based on the philosophy of positivism which views reality or symptoms as causal. The findings of this study are that the emotional value sub-variable has the highest impact, while what is lacking from the culinary tourism values applied in Pesona Kampung Sunda Bandung is prestige value. Customer satisfaction shows very positive results with the highest indicator being the level of conformity to expectations from the place and services presented and the desire to visit again to Pesona Kampung Sunda, so that it is a positive value for business continuity in Pesona Kampung Sunda Bandung.The results showed simultaneous testing where the values of culinary tourism had a significant effect on customer satisfaction by 63.6%, the remaining 36.4% of factors or variants that were not studied.